GLOBAL-SUSTAINMENT ROUTES IN ABSENCE OF PANAMA CANAL ACCESSIBILITY - Bernal, Katrina A. (Monterey, CA; Naval Postgraduate School, 2024)
The Panama Canal is a critical maritime passage that allows naval vessels to transit from the Pacific Ocean to the Atlantic Ocean. What makes the passage favorable is the time and cost efficiency it provides for vessels in transit. Considering the criticality of the Panama Canal, it also begs the question of what potential global sustainment routes look like in the event the Panama Canal is compromised. Recent work analyzes worldwide sustainment routes from ocean to ocean to include the Panama Canal and lost mission days due to adversary interdiction among critical maritime passageways. There are no current plans on analyzing sustainment routes through uncommon passageways such as the Northwest passage and the Cape of Good Hope. In addition, little work has been done on analyzing refueling support within these regions along with potential adversary action against these potential nodes. This thesis is a continuation of analyzing sustainment routes by using a worldwide routing network with an attacker-defender construct that demonstrates the redistribution of naval forces from the East Coast to the western Pacific Ocean. Our decision aid accounts for worldwide routes, replenishment options, 1–2-week extended weather forecasts, and adversary action against port nodes. The goal is to seek further alternative routes for naval ships underway in the event of the complete loss of the Panama Canal. Distribution Statement A. Approved for public release: Distribution is unlimited. Lieutenant, United States Navy